This is probably a super simple question.
Let's say I have an equation
$$ \mathbf{v}^T(\mathbf{a} + \mathbf{b}) = \mathbf{v}^T(\mathbf{c}). $$
Does this imply that
$$ (\mathbf{a} + \mathbf{b}) = \mathbf{c} $$?
Intuitively, I would say that it does. On the other hand, there is no left hand side operation I can come up with that eliminates $\mathbf{v}$. I tried with:
$$ \mathbf{v} = \begin{pmatrix}v_1 \\ v_2\end{pmatrix} $$ $$ \mathbf{x} = \begin{pmatrix}1/v_1\\1/v_2\end{pmatrix} $$ And then $$\mathbf{x}\mathbf{v}^T(\mathbf{a} + \mathbf{b}) = \mathbf{x}\mathbf{v}^T(\mathbf{c}) $$ But this doesn't result in the identity matrix on the left side as I had hoped:
$$ \begin{pmatrix}1/v1\\1/v2\end{pmatrix}\begin{pmatrix}v1\ v2\end{pmatrix} = \begin{pmatrix}1 \ \ v_2/v_1 \\ v_1/v_2 \ 1 \end{pmatrix} $$